Penerapan Deep learning untuk Menanamkan Nilai Ikhlas dalam Pembelajaran Akidah Akhlak Siswa SMP di Era Digital - Nafisah Azka Sabila; Ahmad Bludan Vija; Putri Salma; Ammar; Abdul Fadhil (Yayasan Al-Afif, 2025)
This study addresses the declining understanding of the value of sincerity among junior high school students, a phenomenon significantly exacerbated by digital culture and the increasing need for external validation. This research aims to formulate a conceptual model for applying a Deep Learning approach to instill the value of sincerity in Aqidah Akhlak instruction, ensuring pedagogical relevance to contemporary students. Employing a literature review method, data were synthesized from academic books, research articles, and credible digital sources. The results indicate that Deep Learning facilitated through critical reflection, experiential analysis, and problem-solving enables students to comprehend sincerity comprehensively while providing teachers with valuable insights into student motivational patterns. This approach makes a positive contribution to the development of a sincere, stable, and contextual religious character. The study concludes that the implementation of Deep Learning is most effective when supported by adequate pedagogical readiness and digital literacy among teachers, offering a viable solution for modern religious education.